PENGARUH MEROKOK TERHADAP NILAI ARUS PUNCAKEKSPIRASI PADA PEKERJA SATUAN PENGAMANAN UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN"JAKARTA - Tissa Rafifah Ardiana (2020)
Cigarette caused chronic bronchitis, emphysema, and COPD. Smoking cigarette for a long time and the amount of cigarette consumed a day can affected physiological function of respiratory system which can be assested by peak expiratory flow. Nicotine in cigarette also can affected body mass Index and peak expiratory flow as well. This research wants to know the impact of cigarette and body mass index to peak expiratory score to security workers in UPN "Veteran" Jakarta. This is an observational analysis with cross sectional design and consecutive sampling and analyzed with chi-square. The analysis showed that there was a significant effect of cigarette to peak expiratory flow score (OR = 6.591; 95% CI = 1.111 to 39.108; p = 0.036), but not had a significant effect of BMI to peak expiratory flow score (OR = 1.043; 95% CI = 0.260 - 4.183; p = 0.621).